Storage stability and sourdough acidification kinetic of freeze-dried Lactobacillus curvatus N19 under optimized cryoprotectant formulation - Gul, Latife Betul; Con, Ahmet Hilmi; Gul, Osman (Elsevier BV, 2020)
In this study, the response surface methodology was used to optimize the cryoprotective agent (skimmed milk powder, lactose and sucrose) formulation for enhancing the viability of Lactobacillus curvatus N19 during freeze-drying and storage stability of cells freeze-dried by using optimum formulation was evaluated. Our results showed that the most significant cryoprotective agent influencing the viability of L. curvatus N19 to freezing and freeze-drying was sucrose and skim milk, respectively. The optimal formulation of cryoprotective agents was 20 g/100 mL skim milk, 3.57 g/100 mL lactose and 10 g/100 mL sucrose. Using the optimum formulation during freeze-drying, the cell survival was found more than 98%. Under the optimal conditions, although only storage of the cells at 4 °C for 6 month retained the maximum stability (8.85 log cfu/g), the employed protectant matrix showed promising results at 25 °C (7.89 log cfu/g). The storage stability of cells under optimized conditions was predicted by accelerated storage test, which was demonstrated that the inactivation rate constant of the freeze-dried L. curvatus N19 powder was 9.74 × 10-6 1/d for 4 °C and 2.08 × 10-3 1/d for 25 °C. The loss of specific acidification activity after the storage at 4 and 25 °C was determined.
Keywords: Cryopreservation; Lactobacillus; Cryoprotective Agents; Freeze Drying; Animals; Hydrogen-Ion Concentration